Names, derivational morphology, and Old English gender - Colman, Fran (Adam Mickiewicz University, 2008)
The paper argues that names constitute a primary linguistic category: they do not constitute a subclass of nouns. What have been regarded as formal devices for signalling “name-hood”, “properness”, and so on, are part of a language’s derivational morphology. In this context, it argues that apparent “changes of gender” of Old English nouns are the product of a type of derivational (word-class changing) morphology.